Asymmetric Phase MPCC Interleaving Method for Boost PFC Converter With Enhanced Input Current Harmonic Characteristic - Hee-Jeong Seon; Hyun-Gyu Koh; Yeong-Jun Choi (IEEE Access)
This paper proposes an asymmetric phase model predictive current control (MPCC) interleaving method to improve power density, power factor (PF), and total harmonic distortion (THD) of power factor correction (PFC) converters. The MPCC method operates without a modulator, making it difficult to apply the conventional interleave method. Furthermore, the conventional interleaved method increases dead volume under light load conditions. To solve this problem, this paper proposes to implement the interleaving effect without a modulator by adjusting the timing of the discrete-time model prediction by setting the sampling time of the main phase and the auxiliary phase differently, and to reduce the dead volume by setting the inductance value of the auxiliary phase smaller than the main phase. The sampling period for the auxiliary phase is selected based on the inductance values of the main and auxiliary phases, as well as the main phase’s sampling period, to achieve similar ripple characteristics with a smaller inductor. The proposed method uses a smaller auxiliary inductance to maintain similar input current ripple as the conventional method, and moreover, improves PF and THD by increasing power density and reducing cusp distortion. The performance of the proposed method is verified through experiments on a boosted PFC converter using an Imperix module with 3.3 kW load. The verification results showed that the proposed method achieved improved PF under all load conditions, and improved THD at high load conditions, meeting the IEC-61000-3-2 CLASS A standard.